PERSEPSI GURU TENTANG KEPEMIMPINAN KEPALA SEKOLAH DASAR NEGERI - Rini Syevyilni Wisda (Universitas Negeri Malang, 2021)
Abstract: The background of this research is the leadership of the principal of the State Elementary School Sub-district in carrying out its functions, it is not carried out properly. This study aims to determine the teacher's perception of the principal's leadership in terms of influencing, motivating, moving, and directing. This research method is quantitative. Collecting data using a questionnaire. The sample of this research is teachers of State elemntary School as many as 51 people. The results showed that in general it can be said that the leadership of the principal of the State Elementary School is good with an average percentage of 64.01% of respondents stating always and often. Keywords: Teachers Perception; Principal Leadership Abstrak: Penelitian ini dilatarbelakangi oleh kepemimpinan kepala sekolah Dasar Negeri dalam melaksanakan fungsinya kurang terlaksana sebagaimana mestinya. Penelitian Ini bertujuan untuk mengetahui persepsi guru tentang kepemimpinan kepala sekolah dilihat dari aspek mempengaruhi, memotivasi, menggerakkan, dan mengarahkan. Penelitian ini menggunakan metode Kuantitatif. Pengumpulan data dengan menggunakan angket, Sampel dalam penelitian ini guru SD Sebanyak 51 orang. Hasil Penelitian menunjukkan bahwa secara umum dapat dikatakan bahwa kepemimpinan kepala sekolah Dasar Negeri baik dengan persentase Rata-rata 64,01% responden menyatakan selalu dan sering. Kata Kunci: Persepsi Guru; Kepemimpinan Kepala Sekolah